Pengaruh Model Pembelajaran Mind Mapping terhadap Hasil Belajar Pkn pada Siswa Kelas III SDN 1 Bunigeulis - Nuresa Oskara; Asep Usamah (Edukhasi: Jurnal Inovasi Pendidikan, 2023)
This research aims to determine the Effect of Mind Mapping Learning Model on PkN Learning Outcomes in Grade III Students of SDN 1 Bunigeulis of Hantara District Kuningan District. The study used the One Group Pretest-Posttest Design research method. The subject of this study was a class III number of 16 learners. The instruments used in this study are in the form of test sheets. The results obtained were as follows, the pretest average value was 57.25 while the average posttest score amounted to 82.43. Based on the results of statistical test testing using hypothesis test obtained thit (2,58) > ttab (1,7613), Ha accepted that there is an influence of Mind Mapping Learning Model on PkN Learning Outcomes in Grade III Students of SDN 1 Bunigeulis District Hantara.